Constitutive model of duplex stainless steel S22053 and its weld under cyclic large plastic strain loading. (June 2023) - Luo, Jing; Li, Shuailing; Mao, Lingtao; Shi, Gang
Abstract: This study investigated the mechanical properties and constitutive models of duplex stainless steel S22053 under cyclic large plastic strain loading. To this end, smooth round bar specimens of the base metal, deposited metal, and heat-affected mixing zone material were tested under monotonic tensile loading and cyclic loading. Furthermore, the failure modes and stress–strain curves of the specimens were analysed. Based on the test results of the smooth round bar specimens under cyclic symmetric constant amplitude and monotonic tensile loading, the N3L1 and S10 parameters of the Chaboche model for duplex stainless steel S22053 were calibrated, respectively. Then, the accuracy of the calibrated Chaboche model was verified against the test results of the smooth round bar and circular notched bar specimens. The results showed that the base metal and heat-affected mixing zone material have higher ductility, and the strength of the deposited metal is the highest. Furthermore, the N3L1 parameters can accurately simulate the behavior of smooth round bar specimens under cyclic medium plastic strain loading, while the S10 parameters are more suitable for simulating the mechanical response of circular notched bar specimens under cyclic large plastic strain loading. The accuracy of the Chaboche model depends on the matching of the loading strain range of the test data for calibrating the model with that of the simulation cases. The results of this study provide fundamental data for analysing the seismic and ductile fracture performance of duplex stainless steel and its welded structures. Graphical abstract: Unlabelled Image Highlights: Mechanical properties of the S22053 base metal, deposited metal, and heat-affected mixing zone material are analysed. Methods to calibrate the cyclic constitutive model parameters using cyclic and monotonic test data are proposed. ULCF tests of circular notched bar specimens are simulated and compared. Constitutive parameters suitable for large plastic strain cyclic loading are proposed and assessed.